Alkaline batteries
By optimizing the zinc alloy particle proportions, bulk density, and incorporating a gelling agent and surfactant in the negative electrode, the alkaline dry battery stabilizes OCV against temporary drops, reducing defect rates and improving manufacturing efficiency.
Patent Information
- Application Number
- JP2023546771
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-08
- Filing Date
- 2022-05-23
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-05-23
AI Technical Summary
Alkaline dry batteries experience a temporary decrease in open circuit voltage (OCV) during manufacturing, leading to false defect determinations and increased costs due to shock-induced changes in conductive paths within the negative electrode.
The alkaline dry battery design includes specific proportions of zinc alloy particles passing through a 75 μm mesh (9 to 28% by mass), a zinc alloy powder content of 60 to 64% by mass, a bulk density of 2.7 to 3.2 g/cm³, and the presence of a gelling agent and surfactant in the negative electrode to stabilize the conductive paths and suppress temporary OCV drops.
This configuration effectively prevents the misclassification of good batteries as defective by stabilizing the OCV, reducing manufacturing defects to 2% or less, and enhancing the reliability and productivity of the alkaline dry batteries.
Smart Images

Figure 0007620897000004 
Figure 0007620897000005 
Figure 0007620897000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to alkaline dry batteries. [Background technology]
[0002] Alkaline dry batteries (alkaline manganese dry batteries) are widely used because they have a larger battery capacity and can extract a larger current than manganese dry batteries. An alkaline dry battery usually includes a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an alkaline electrolyte. The positive electrode contains manganese dioxide as a positive electrode active material. Various proposals have been made to improve the characteristics of alkaline dry batteries.
[0003] Patent Document 1 (Patent No. 6335531) discloses "an alkaline battery comprising an alkaline electrolyte, a gelling agent, and a gelled negative electrode containing a powder mainly composed of zinc housed in a bottomed cylindrical positive electrode can, the powder containing particles having a particle size of 75 μm or less in the range of 25 to 40 mass %, the gelling agent containing a water-absorbent resin having a water absorption capacity of 37 times or more the alkaline electrolyte (water absorption capacity of a 40 mass % potassium hydroxide aqueous solution), the positive electrode can being supported at a height of 1 m so that its axial direction is horizontal to the ground, and the battery is allowed to freely fall from the supported position onto a concrete floor, the maximum current upon short circuit being 15 A or more."
[0004] Patent Document 2 (Patent No. 4729321) discloses "an alkaline battery in which a cylindrical separator is loaded inside an annular positive electrode mixture loaded into a bottomed cylindrical battery can with the lower side as the bottom, and a negative electrode gel containing zinc or a zinc alloy as a negative electrode active material is filled only inside this separator, and a rod-shaped negative electrode current collector connected to the lower surface of a negative electrode terminal plate that seals the opening of the battery can extends in the cylindrical axial direction of the battery can and penetrates into the center of the negative electrode gel, wherein a relatively high-viscosity negative electrode gel layer and a relatively low-viscosity negative electrode gel layer are present in the negative electrode gel in a stacked state with the extension direction of the cylindrical axis as the stacking direction, thereby suppressing flow of the negative electrode gel."
[0005] Patent Document 3 (JP 2014-7002 A) discloses "an alkaline battery comprising a hollow cylindrical positive electrode, a gelled negative electrode containing zinc and a gelling agent, a separator arranged between the positive electrode and the gelled negative electrode, and an alkaline electrolyte contained in a bottomed cylindrical battery case, wherein the gelling agent is made of one type of polyacrylate, the concentration of the polyacrylate in the gelled negative electrode is in the range of 0.4 to 1.0 mass%, the concentration of the zinc in the gelled negative electrode is in the range of 55 to 70 mass%, and the bulk density of the zinc is in the range of 2.50 to 3.00 g / ml."
[0006] Patent Document 4 (JP 2014-170652 A) discloses a zinc alloy powder for alkaline batteries, which contains "170 to 230 ppm of Al, 121 to 225 ppm or less of Bi, 150 to 250 ppm or less of In, and 10 ppm or less of at least one of inevitable impurities of magnesium, iron, copper, lead, nickel, cobalt, and manganese, with the remainder being zinc, wherein the ratio of powder of 200 mesh or less is 10 mass% or more, the ratio of powder of 200 to 150 mesh is 9 to 20 mass%, the ratio of powder of 150 to 100 mesh is 18 to 40 mass%, the ratio of powder of 100 to 50 mesh is 20 to 40 mass%, the ratio of powder of 50 to 40 mesh is 3 to 17 mass%, and the ratio of powder of 40 mesh or more is less than 7 mass%, and the total ratio of the powders is 100% by mass." [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 6335531 [Patent Document 2] Patent No. 4729321 [Patent Document 3] JP 2014-7002 A [Patent Document 4] Patent Publication No. 2014-170652 Summary of the Invention
[0008] An alkaline dry battery according to one aspect of the present disclosure includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The negative electrode includes zinc alloy powder, a gelling agent, a surfactant, and an electrolyte. The proportion of zinc alloy particles passing through a mesh having an opening of 75 μm in the zinc alloy powder is in the range of 9 to 28 mass %. The bulk density of the zinc alloy powder is 2.7 to 3.2 g / cm. 3 The content of the zinc alloy powder in the negative electrode is in the range of 60 to 64 mass %.
[0009] This alkaline dry battery can suppress a temporary drop in open circuit voltage. [Brief description of the drawings]
[0010] [Figure 1A] FIG. 1A is a conceptual diagram of zinc alloy powder for an alkaline dry battery according to an embodiment. [Figure 1B] FIG. 1B is an enlarged cross-sectional view of a mesh according to an embodiment. [Diagram 2] FIG. 2 is a partially exploded cross-sectional view showing an example of an alkaline dry battery according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the following, the embodiments according to the present disclosure will be described by way of examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and other materials may be applied as long as the invention according to the present disclosure can be implemented. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "numerical value A or more and numerical value B or less." In the following description, when one or more lower limit values and one or more upper limit values related to specific physical properties or conditions are exemplified, any one of the one or more exemplified lower limit values and any one of the one or more exemplified upper limit values can be arbitrarily combined to form the upper limit and the lower limit, as long as the lower limit is not equal to or greater than the upper limit.
[0012] (Alkaline battery) The alkaline dry battery according to this embodiment includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. The negative electrode includes zinc alloy powder, a gelling agent, a surfactant, and an electrolyte. FIG. 1A is a conceptual diagram of zinc alloy powder 31 in the alkaline dry battery according to this embodiment. FIG. 1B is an enlarged cross-sectional view of a mesh 21 according to this embodiment. The mesh 21 has an opening Aw. The ratio of zinc alloy particles 32 passing through the mesh 21 having an opening Aw of 75 μm in the zinc alloy powder 31 is in the range of 9 to 28 mass %. The bulk density of the zinc alloy powder 32 is 2.7 to 3.2 g / cm. 3 The content of zinc alloy powder 32 in the negative electrode is in the range of 60 to 64 mass %. Hereinafter, the ratio of zinc alloy particles 32 that pass through mesh 21 with opening Aw of 75 μm in zinc alloy powder 31 is referred to as ratio R(75). Note that an alkaline dry battery contains electrolyte present in portions other than the negative electrode in addition to electrolyte contained in the negative electrode.
[0013] In the manufacture of alkaline dry batteries, the manufactured alkaline dry batteries are usually tested. For example, the OCV (Open Circuit Voltage) of the alkaline dry batteries is measured. In the OCV measurement, batteries whose OCV is below a threshold value are treated as defective. Therefore, in the OCV measurement, alkaline dry batteries with no defects are judged as good products, and alkaline dry batteries with defects are judged as defective products.
[0014] However, as a result of the study by the inventors of the present application, a new problem was found in that the OCV temporarily drops during the measurement of the OCV, causing a good alkaline dry battery to be judged as defective. This problem was not known in the past. Judging a battery that has no defects as defective leads to an increase in manufacturing costs, and therefore needs to be avoided.
[0015] OCV is also called open circuit voltage, in other words, it can be said to be the voltage of the battery when no current is flowing. OCV corresponds to the difference between the OCP (Open Circuit Potential) of the positive electrode and the OCP of the negative electrode. The OCP of the negative electrode changes depending on the potential of the zinc alloy particles, which are the negative electrode active material. When the negative electrode contains a surfactant, it is thought that the surface potential of the zinc alloy particles with a large amount of surfactant attached will be high. When the negative electrode contains zinc alloy particles with a small amount of surfactant attached and zinc alloy particles with a large amount of surfactant attached, the negative electrode contains zinc alloy particles with a high surface potential and zinc alloy particles with a low surface potential. Usually, the OCP of the negative electrode is determined by the zinc alloy particles with a low surface potential. However, when an impact is applied to an alkaline dry battery, the path connecting the zinc alloy particles with a low surface potential is cut, and it is thought that the effect of the zinc alloy particles with a high surface potential on the OCP becomes large. Therefore, the OCP of the negative electrode may change due to the impact given to the alkaline dry battery during the OCV test, and as a result, the OCV may temporarily decrease. The temporarily decreased OCV will recover after a certain amount of time has passed. This recovery indicates that the OCV drop is not due to a defective battery, but is due to a temporary change in the conductive path in the negative electrode, and therefore it is necessary to suppress the OCV drop to avoid defective alkaline batteries.
[0016] In this specification, a temporary drop in OCV refers to a phenomenon in which the OCV(1) measured after an alkaline battery is assembled (for example, for a battery within 7 days) temporarily drops due to impact. When batteries are mass-produced, the batteries are continuously processed, and therefore the batteries are subjected to impact during OCV measurement. A temporary drop in OCV refers to the OCV(1) being the OCV that is determined to be a defective battery, and the OCV measured after a certain period of time (hereinafter sometimes referred to as "OCV(2)") being the OCV that is determined to be a good battery. An OCV that is determined to be a defective battery is a voltage that is equal to or lower than (mode V-3mV) relative to the mode V of the OCV of a large number (for example, 100 or more) of alkaline dry batteries manufactured under the same conditions. In other words, if OCV(1) is equal to or lower than (mode V-3mV), the battery is determined to be defective. If the OCV(2) of a battery determined to be defective is measured again after 3 minutes or more have passed without any shock since the measurement of the OCV(1), and the measured value is higher than the most frequent value V-3mV, the battery is determined to have a temporary drop in OCV. The OCV is measured at room temperature (approximately 25°C). The most frequent value V of OCV means the OCV value that is most frequently distributed when the OCV is measured with three significant digits after the decimal point when the OCV is expressed in volts (V).
[0017] A temporary drop in OCV is likely to occur during the short time after assembly when the battery's constituent materials are not yet fully mixed. After a certain amount of time has passed since assembly, the battery's constituent materials will have fully mixed, making the temporary drop in OCV less likely to occur. If the negative electrode does not contain a surfactant, the temporary drop in OCV will not occur.
[0018] By including a surfactant in the negative electrode, it is possible to prevent the zinc alloy powder from corroding in the alkaline electrolyte and generating hydrogen gas. If hydrogen gas is generated in the battery, it can cause an increase in the battery's internal pressure and electrolyte leakage. Therefore, in order to improve the reliability of alkaline dry batteries, it is important that the negative electrode includes a surfactant.
[0019] The alkaline dry battery according to the present disclosure satisfies the following conditions (1) to (4). (1) The proportion R(75) of zinc alloy particles 32 passing through a mesh with an opening of 75 μm in the zinc alloy powder 31 is in the range of 9 to 28 mass %. (2) The content of zinc alloy powder 31 in the negative electrode is in the range of 60 to 64 mass %. (3) The bulk density of the zinc alloy powder 31 is 2.7 to 3.2 g / cm 3 is in the range. (4) The negative electrode includes zinc alloy powder 31, a gelling agent, a surfactant, and an electrolyte.
[0020] By satisfying the above conditions (1) to (4), it is possible to suppress a temporary drop in OCV and prevent a non-defective product from being determined to be defective. Although the reason for this is not clear, as shown in the examples, by satisfying the above conditions (1) to (4), it is possible to reliably suppress a temporary drop in OCV.
[0021] The reason why the temporary drop in OCV can be suppressed by satisfying the above conditions (1) to (4) can be considered as follows. First, it is believed that the viscosity of the negative electrode can be increased by the above conditions (1) and (2). Specifically, the viscosity of the negative electrode can be increased by setting the ratio R(75) to 9 mass% or more and setting the content of zinc alloy powder in the negative electrode to 60 mass% or more. It is believed that the increase in the viscosity of the negative electrode can suppress the conductive path between the zinc alloy particles from being cut.
[0022] By satisfying the above condition (3), it is possible to particularly suppress a temporary decrease in OCV. Although the reason for this is not clear, it is believed that by satisfying the above condition (3), the number of contact points between the zinc alloy particles constituting the zinc alloy particle 31 is within an appropriate range. If the number of contact points between the zinc alloy particles is too large or too small, when the conductive path between the zinc alloy particles is cut by an impact, a conductive path passing through the zinc alloy particles at a high potential is likely to be formed, and the OCP of the negative electrode is thought to increase.
[0023] Furthermore, by including a gelling agent in the negative electrode, the movement of zinc alloy particles when the alkaline dry battery is subjected to an impact can be suppressed, and as a result, a temporary decrease in OCV can be particularly suppressed.
[0024] In order to suppress the temporary drop in OCV, it is necessary to satisfy all of the above conditions (1) to (4). It is believed that the above conditions (1) to (4) each affect each other to exert a synergistic effect, suppressing the temporary drop in OCV. There are countless factors that may affect the temporary drop in OCV, and it is extremely difficult to identify those factors or find a solution. However, as a result of focusing on the contact points of zinc alloy powder particles and studying them, the present inventors have found that the temporary drop in OCV can be suppressed by a combination of the above conditions (1) to (4), which is difficult to predict. The alkaline dry battery according to the present disclosure is based on this new finding.
[0025] Regarding condition (1), the mesh 21 with an opening of 75 μm can be a standard sieve wire mesh with an opening Aw of 75 μm as specified in JIS Z 8801. By setting the ratio R(75) of the zinc alloy particles 32 that pass through the mesh 21 with an opening of 75 μm in the zinc alloy powder 31 to 9 mass% or more and 29 mass% or less, a temporary decrease in OCV can be suppressed. Furthermore, by setting the ratio R(75) to 28 mass% or less, gas generation from minute zinc alloy particles can be suppressed, and as a result, the risk of leakage can be reduced. Therefore, the ratio R(75) is preferably 28 mass% or less. The ratio R(75) may be 15 mass% or more.
[0026] Regarding condition (2), the content of zinc alloy powder in the negative electrode refers to the proportion (mass ratio) of zinc alloy powder in the negative electrode, more specifically, the proportion (mass ratio) of zinc alloy powder to the total mass of the components of the negative electrode (zinc alloy powder, electrolyte, gelling agent, surfactant, and other optional additives).
[0027] By setting the content of zinc alloy powder in the negative electrode to 60% by mass or more and 65% by mass or less, a temporary decrease in OCV can be suppressed. Furthermore, by setting the content to 64% by mass or less, productivity can be increased. Therefore, the content is preferably 64% by mass or less. The content may be 61% by mass or more, 62% by mass or more, or 63% by mass or more. The content may be 63% by mass or less.
[0028] Regarding condition (3), the bulk density can be measured in accordance with JIS Z 2504 (hole diameter φ: 2.5 mm). The lower the bulk density of the powder, the bulkier the particles that make up the powder. The bulk density of zinc alloy powder is 2.7 g / cm 3 More than 2.8g / cm 3 More than 2.9g / cm 3 or more than 3.0g / cm 3 The bulk density may be 3.2 g / cm or more. 3 Less than or equal to 3.1 g / cm 3 or less than 3.0g / cm 3 It may be the following.
[0029] Examples of the gelling agent include cross-linked polyacrylic acid and cross-linked polyacrylic acid partial sodium salt, and may include other gelling agents. The gelling agent may include only cross-linked polyacrylic acid, or may include cross-linked polyacrylic acid and cross-linked polyacrylic acid partial sodium salt. The gelling agent may include only cross-linked polyacrylic acid and cross-linked polyacrylic acid partial sodium salt.
[0030] When the gelling agent contains crosslinked polyacrylic acid and partial sodium salt of crosslinked polyacrylic acid, the mass ratio thereof may satisfy (crosslinked polyacrylic acid):(partial sodium salt of crosslinked polyacrylic acid)=1:0.5-4 (e.g., 1:1-3). This range can particularly suppress a temporary decrease in OCV.
[0031] The proportion of the gelling agent in the total of the positive electrode, negative electrode, and electrolyte of the alkaline dry battery may be in the range of 0.1 mass % to 0.4 mass % (for example, in the range of 0.2 mass % to 0.3 mass %).
[0032] The surfactant preferably includes an anionic surfactant containing an ethylene oxide group (-CH2-CH2-O-). Hereinafter, the anionic surfactant may be referred to as "anionic surfactant (S)."
[0033] The anionic surfactant (S) may contain a polyoxyethylene chain (multiple ethylene oxide groups bonded in a linear chain), a hydrophobic group bonded to one end of the polyoxyethylene chain (e.g., an oxygen atom), and an anionic group bonded to the other end of the polyoxyethylene chain (e.g., a carbon atom). The n ethylene oxide groups bonded in a linear chain are represented by the formula (-CH2-CH2-O-). n It is expressed as:
[0034] The number of ethylene oxide groups bonded in a linear fashion may be 3 or more, 4 or more, 6 or less, 5 or less, or 3 or 4. The number of carbon atoms in the hydrophobic group may be 4 or more, 7 or more, 10 or more, 12 or more, and 20 or less, 18 or less, or 15 or less. The hydrophobic group may be a hydrocarbon group (e.g., an alkyl group). Examples of the hydrophobic group include a hydrocarbon group (e.g., an alkyl group such as a linear alkyl group) having 4 or more and 15 or less carbon atoms (e.g., in the range of 10 to 15 or 12 to 15). Examples of the anionic group include a phosphate group, a carboxylate group, and the like. The anionic surfactant (S) may include 3 or more and 6 or less ethylene oxide groups bonded in a linear fashion and a hydrophobic group having a carbon number in the range of 5 to 15. This configuration can particularly suppress a temporary decrease in OCV. In this case, the anionic group may be a phosphate group.
[0035] The ratio of the anionic surfactant (S) to the total of the positive electrode, negative electrode, and electrolyte of the alkaline dry battery may be in the range of 0.0001% by mass to 0.01% by mass (for example, in the range of 0.0002% by mass to 0.001% by mass). Note that a part of the anionic surfactant added to the negative electrode migrates to the electrolyte and the positive electrode.
[0036] The alkaline dry battery according to the present disclosure includes a positive electrode, a negative electrode, a separator, and an electrolyte, and may include other components as necessary. Examples of the components of the alkaline dry battery according to the present disclosure are described below.
[0037] (positive electrode) The positive electrode contains manganese dioxide as a positive electrode active material. The positive electrode usually contains a positive electrode active material and a conductive material, and further contains a binder as necessary. The positive electrode may be formed by pressure molding the positive electrode mixture into a cylindrical body (positive electrode pellet). The positive electrode mixture contains, for example, a positive electrode active material, a conductive material, and an alkaline electrolyte, and further contains a binder as necessary. After being housed in the case body, the cylindrical body may be pressed so as to be in close contact with the inner wall of the case body.
[0038] A preferred example of manganese dioxide as a positive electrode active material is electrolytic manganese dioxide, but natural manganese dioxide or chemical manganese dioxide may also be used. The crystal structure of manganese dioxide includes α-type, β-type, γ-type, δ-type, ε-type, η-type, λ-type, and ramsdellite-type.
[0039] The average particle size (D50) of the manganese dioxide powder may be in the range of, for example, 25 μm to 60 μm, from the viewpoint of easily ensuring the filling property of the positive electrode and the diffusibility of the electrolyte in the positive electrode.
[0040] From the viewpoint of moldability and suppression of expansion of the positive electrode, the BET specific surface area of manganese dioxide is, for example, 20 m 2 / g~50m 2 The BET specific surface area can be measured, for example, by using a specific surface area measuring device using a nitrogen adsorption method.
[0041] The conductive material may be a conductive carbon material. Examples of the conductive carbon material include carbon black (such as acetylene black) and graphite. Examples of graphite include natural graphite and artificial graphite. The conductive material may be in powder form. The average particle size (D50) of the conductive material may be in the range of 3 μm to 20 μm. The content of the conductive material in the positive electrode may be in the range of 3 parts by mass to 10 parts by mass (for example, in the range of 5 parts by mass to 9 parts by mass) with respect to 100 parts by mass of manganese dioxide.
[0042] A silver compound may be added to the positive electrode to absorb hydrogen generated inside the battery. Examples of silver compounds include silver oxide (Ag2O, AgO, Ag2O3, etc.) and silver-nickel composite oxide (AgNiO2).
[0043] (Negative electrode) The negative electrode contains zinc alloy powder as a negative electrode active material. From the viewpoint of corrosion resistance, the zinc alloy may contain at least one selected from the group consisting of indium, bismuth, and aluminum. The indium content in the zinc alloy may be in the range of, for example, 0.01% by mass to 0.1% by mass. The bismuth content in the zinc alloy may be in the range of, for example, 0.003% by mass to 0.02% by mass. The aluminum content in the zinc alloy may be in the range of, for example, 0.001% by mass to 0.03% by mass. From the viewpoint of corrosion resistance, the content of elements other than zinc in the zinc alloy may be in the range of 0.025% by mass to 0.08% by mass.
[0044] The average particle size (D50) of the zinc alloy powder may be in the range of 100 μm to 200 μm (for example, in the range of 110 μm to 160 μm) from the viewpoint of the filling property of the negative electrode and the diffusibility of the electrolyte in the negative electrode. In this specification, the average particle size is the median diameter (D50) at which the cumulative volume becomes 50% in the volume-based particle size distribution. The median diameter is determined, for example, by using a laser diffraction / scattering type particle size distribution measuring device.
[0045] As described above, the negative electrode includes a zinc alloy powder, a gelling agent, a surfactant, and an electrolyte. The negative electrode can be formed by mixing the zinc alloy powder, the gelling agent, the surfactant, and the electrolyte. From the viewpoint of dispersing the additives (gelling agent, surfactant, etc.) more uniformly in the negative electrode, it is preferable that the additives are added in advance to the electrolyte used to prepare the negative electrode. The electrolyte can be an electrolyte (alkaline electrolyte) described later.
[0046] In order to improve corrosion resistance, a compound containing a metal having a high hydrogen overvoltage, such as indium or bismuth, may be appropriately added to the negative electrode.
[0047] (Negative electrode current collector) The alkaline dry battery of the present disclosure may include a negative electrode current collector inserted into the negative electrode. The material of the negative electrode current collector may be a metal (simple metal or alloy). The material of the negative electrode current collector preferably contains copper, and may be an alloy containing copper and zinc (e.g., brass). The negative electrode current collector may be plated with tin or the like as necessary.
[0048] (Separator) As the separator, a nonwoven fabric mainly made of fibers or a microporous film made of resin is used. Examples of the fiber material include cellulose, polyvinyl alcohol, etc. The nonwoven fabric may be formed by mixing cellulose fibers and polyvinyl alcohol fibers, or may be formed by mixing rayon fibers and polyvinyl alcohol fibers. Examples of the microporous film material include resins such as cellophane and polyolefin. The thickness of the separator may be in the range of 200 μm to 300 μm. When the separator is thin, a plurality of separators may be stacked to adjust the thickness to the above thickness.
[0049] (electrolyte) As the electrolyte (alkaline electrolyte), for example, an alkaline aqueous solution containing potassium hydroxide is used. The concentration of potassium hydroxide in the alkaline electrolyte is preferably in the range of 30 to 50 mass % (for example, in the range of 30 to 40 mass %). The alkaline electrolyte may contain lithium hydroxide (LiOH), sodium hydroxide (NaOH), cesium hydroxide (CsOH), rubidium hydroxide (RbOH), etc.
[0050] The alkaline electrolyte may contain a surfactant. The use of a surfactant can enhance the dispersibility of the negative electrode active material particles. The surfactant may be one exemplified for the negative electrode. The content of the surfactant in the alkaline electrolyte is usually in the range of 0 to 0.5% by mass (for example, in the range of 0 to 0.2% by mass).
[0051] (battery housing) There is no particular limitation on the battery housing, and a housing according to the shape of the battery may be used. There is no particular limitation on the shape of the alkaline dry battery according to this embodiment, and it may be cylindrical or coin-shaped (including button-shaped). The battery housing usually includes a battery case, a negative electrode terminal plate, and a gasket. For example, a cylindrical metal case with a bottom is used as the battery case. For example, a nickel-plated steel plate is used as the metal case. In order to reduce the contact resistance between the positive electrode and the battery case, the inner surface of the battery case may be coated with a carbon film. The negative electrode terminal plate can be formed of the same material as the metal case, for example, a nickel-plated steel plate.
[0052] Examples of the gasket material include polyamide, polyethylene, polypropylene, polyphenyl ether, polyphenylene ether, etc. From the viewpoint of corrosion resistance against alkaline electrolyte, the gasket material is preferably polyamide-6,6, polyamide-6,10, polyamide-6,12, and polypropylene. The gasket usually has a ring-shaped thin portion.
[0053] (Manufacturing method of alkaline dry batteries) The method for producing the alkaline dry battery according to the present embodiment is not particularly limited, and the battery may be produced by a known method. The negative electrode can be produced by mixing materials constituting the negative electrode, as will be described in the Examples.
[0054] The ratio R(75) can be controlled by changing the mixing ratio of zinc alloy powder 32 that has passed through a mesh with an opening of 75 μm and zinc alloy powder 33 that has not passed through the mesh (see FIG. 1A). The average particle size of the zinc alloy powder may be controlled by changing the mixing ratio of zinc alloy powder that has passed through various meshes.
[0055] The bulk density of zinc alloy powder can be controlled by changing the average particle size, particle size distribution, and shape of the zinc alloy powder. Zinc alloy powders with various average particle sizes, particle size distributions, and shapes are available on the market, so the bulk density can be controlled by using them. In the case of zinc alloy powder with a uniform particle size, the larger the particle size, the smaller the bulk density generally becomes.
[0056] The content of each component in the negative electrode (for example, the content of zinc alloy powder) can be controlled by changing the mixing ratio of each component when constructing the negative electrode.
[0057] An example of an embodiment according to the present disclosure will be specifically described below with reference to the drawings. The above-mentioned components can be applied to the components of the alkaline dry battery of the example described below. In addition, the components of the alkaline dry battery of the example described below can be modified based on the above description. In addition, the matters described below may be applied to the above-mentioned embodiment.
[0058] (Embodiment 1) 2 shows a partially exploded cross-sectional view of an alkaline dry battery 10 with an inside-out structure according to embodiment 1. The cylindrical alkaline dry battery 10 includes a battery case 1, and a positive electrode 2, a negative electrode (gelled negative electrode) 3, a separator 4, and an electrolyte 11 that are disposed in the battery case 1.
[0059] The battery case 1 is a cylindrical case with a bottom, and functions as a positive electrode terminal. The positive electrode 2 is hollow cylindrical, and is disposed so as to contact the inner wall of the battery case 1. The negative electrode 3 is disposed in the hollow portion of the positive electrode 2. The separator 4 is disposed between the positive electrode 2 and the negative electrode 3. The negative electrode has the above-mentioned configuration.
[0060] The separator 4 is composed of a cylindrical separator 4a and a bottom paper 4b. The separator 4a is disposed along the inner surface of the hollow part of the positive electrode 2, and separates the positive electrode 2 from the negative electrode 3. The bottom paper 4b is disposed at the bottom of the hollow part of the positive electrode 2, and separates the negative electrode 3 from the battery case 1.
[0061] The opening of the battery case 1 is sealed by a sealing unit 9. The sealing unit 9 includes a gasket 5, a negative electrode current collector 6, and a negative electrode terminal plate 7 that functions as a negative electrode terminal. The negative electrode current collector 6 has a nail shape having a head and a body. The negative electrode current collector 6 contains copper, for example, and may be made of an alloy containing copper and zinc, such as brass. The negative electrode current collector 6 may be plated with tin, as necessary. The body of the negative electrode current collector 6 is inserted into a through hole provided in the center of the gasket 5 and is inserted into the negative electrode 3. The head of the negative electrode current collector 6 is welded to the flat part in the center of the negative electrode terminal plate 7.
[0062] The open end of the battery case 1 is crimped to the peripheral edge (flange) of the negative electrode terminal plate 7 via the peripheral edge of the gasket 5. The outer surface of the battery case 1 is covered with an exterior label 8. The battery case 1, the gasket 5, and the negative electrode terminal plate 7 constitute a battery housing. The positive electrode 2, the negative electrode 3, the separator 4, and the alkaline electrolyte 11 are disposed within the battery housing.
[0063] There is no particular limitation on the method for assembling the alkaline dry battery 10, and conventional techniques can be applied as necessary. For example, the alkaline dry battery 10 may be assembled according to the procedure described in the following embodiment.
[0064] <Example> The alkaline dry battery of the present disclosure will be described in further detail with reference to examples.
[0065] (Experimental Example 1) In Experimental Example 1, a number of alkaline dry batteries having different negative electrodes were produced and evaluated according to the following procedures (1) to (4).
[0066] (1) Preparation of electrolyte 11 (alkaline electrolyte) As the alkaline electrolyte 11, an alkaline aqueous solution containing potassium hydroxide (concentration: 33% by mass) and zinc oxide (concentration: 2% by mass) was prepared.
[0067] (2) Preparation of the positive electrode A mixture was obtained by mixing manganese dioxide (positive electrode active material) and graphite (conductive material). They were mixed in a mass ratio of manganese dioxide:graphite = 100:6. For the manganese dioxide, electrolytic manganese dioxide powder (average particle size (D50): 40 μm) was used. For the graphite, graphite powder (average particle size (D50): 8 μm) was used.
[0068] The electrolyte was added to the mixture, thoroughly stirred, and then compression-molded into flakes to obtain a positive electrode mixture. The mass ratio of the mixture to the electrolyte was 100:1.5. The electrolyte was the same as the alkaline electrolyte prepared in (1) above.
[0069] Next, the flake-like positive electrode mixture was crushed to form granules, which were then classified using a 10 to 100 mesh sieve to obtain granules. The obtained granules were press-molded into a hollow cylindrical shape (height 10.8 mm) to obtain a positive electrode pellet (mass 2.9 g). Four of these positive electrode pellets were produced.
[0070] (3) Preparation of the negative electrode Zinc alloy powder, a surfactant, a gelling agent, and an electrolyte were mixed to obtain a gelled negative electrode. Materials other than the zinc alloy powder were mixed in a mass ratio of surfactant:gelling agent:electrolyte=0.005:2.4:100. In Experimental Example 1, a number of negative electrodes were produced by varying the content of zinc alloy powder in the negative electrode and the proportion R(75) of zinc alloy particles in the zinc alloy powder that pass through a mesh with a mesh size of 75 μm to obtain the values shown in Table 1. In all negative electrodes, the bulk density of the zinc alloy powder was 3.2 g / cm. 3 The electrolyte used was the same as the alkaline electrolyte prepared in (1) above. The negative electrode active material used was a zinc alloy powder containing 0.02% by mass of indium, 0.01% by mass of bismuth, and 0.005% by mass of aluminum. The surfactant used was an anionic surfactant. The gelling agent used was a mixture of cross-linked polyacrylic acid and partial sodium salt of cross-linked polyacrylic acid.
[0071] (4) Assembling Battery A1 Using the above components, an alkaline dry battery was assembled by the following method. The procedure for assembling the battery will be described with reference to FIG. 2. First, a coating agent (product name: Bunny Height) manufactured by Nippon Graphite Co., Ltd. was applied to the inner surface of a bottomed cylindrical case made of nickel-plated steel sheet to form a carbon coating having a thickness of about 10 μm, and a battery case 1 was obtained. Next, four positive electrode pellets were inserted vertically into the battery case 1, and then pressure was applied to form a positive electrode 2 in a state of being in close contact with the inner wall of the battery case 1. A bottomed cylindrical separator 4 was placed inside the positive electrode 2, and then the alkaline electrolyte prepared in (1) above was injected and impregnated into the separator 4. This state was left for a predetermined time, and the alkaline electrolyte was allowed to permeate from the separator 4 to the positive electrode 2. Then, 6.4 g of a gelled negative electrode 3 was filled inside the separator 4. For the negative electrode 3, any one of the above-mentioned multiple negative electrodes was used.
[0072] The separator 4 was formed using a cylindrical separator 4a and a bottom paper 4b. A nonwoven fabric sheet mainly made of rayon fiber and polyvinyl alcohol fiber (mass ratio 1:1) was used for the cylindrical separator 4a and the bottom paper 4b.
[0073] The negative electrode current collector 6 was formed by pressing a common brass into a nail shape and then tin-plating the surface. The head of the negative electrode current collector 6 was electrically welded to a negative electrode terminal plate 7 made of nickel-plated steel. Then, the body of the negative electrode current collector 6 was pressed into the central through hole of a gasket 5 made mainly of polyamide-6,12. In this way, a sealing unit 9 consisting of the gasket 5, the negative electrode current collector 6, and the negative electrode terminal plate 7 was produced. The gasket 5 in FIG. 2 has a ring-shaped thin-walled portion 5a.
[0074] Next, the sealing unit 9 was placed in the opening of the battery case 1. At this time, the body of the negative electrode current collector 6 was inserted into the negative electrode 3. Next, the opening end of the battery case 1 was crimped to the peripheral edge of the negative electrode terminal plate 7 so as to sandwich the gasket 5, thereby sealing the opening of the battery case 1. In this manner, the positive electrode 2, the negative electrode 3, the separator 4, and the alkaline electrolyte 11 were placed in the battery housing.
[0075] Next, the outer surface of the battery case 1 was covered with an exterior label 8. In this manner, a number of alkaline dry batteries having different negative electrodes were produced.
[0076] (OCV measurement) The OCV of the produced batteries was measured at room temperature (about 25°C) within 7 days after production. Batteries with an OCV value 3mV or more lower than the most frequent OCV value V were determined to be defective. 100 alkaline dry batteries with different negative electrodes were produced and evaluated. The evaluation results are shown in Table 1. The "content of zinc alloy powder" in Table 1 indicates the content of zinc alloy powder in the negative electrode. Table 1 shows the results of measuring the OCV of 25 types of alkaline dry batteries with different zinc alloy powder contents in the range of 59-65% and ratios R(75) in the range of 8-29%. The values of 0-3% in Table 1 indicate the percentage of batteries determined to be defective for each battery with different negative electrodes.
[0077] [Table 1]
[0078] In addition, when the batteries that were judged to be defective were left for a certain period of time and their OCVs were measured again, none of the batteries were judged to be defective. Therefore, it is believed that the defectiveness judgement in the first OCV measurement was due to a temporary drop in OCV.
[0079] The proportion of products judged as defective due to a temporary drop in OCV is preferably 2% or less. Therefore, it is preferable that the content of zinc alloy powder is in the range of 60-65% and the proportion R(75) is in the range of 9-29%. For the reasons mentioned above, it is particularly preferable that the content of zinc alloy powder is in the range of 60-64% and the proportion R(75) is in the range of 9-28%.
[0080] In addition, among the above batteries, the battery with a ratio R(75) of 9% and a zinc alloy powder content of 59%, and the battery with a ratio R(75) of 8% and a zinc alloy powder content of 63% had a bulk density of 2.7 g / cm 3 ~3.2g / cm 3 The bulk density was changed within the range of 2.7 g / cm3 and the same evaluation was carried out. 3 ~3.2g / cm 3 Within this range, the rate of defective products due to a temporary drop in OCV was reduced to 2% or less.
[0081] (Experimental Example 2) In Experimental Example 2, three types of negative electrodes were prepared by changing the type of gelling agent. Except for the type of gelling agent, the negative electrodes were prepared under the same conditions and methods as in Experimental Example 1. In these negative electrodes, the ratio R(75) was set to 9 mass%, and the bulk density of the zinc alloy powder was set to 3.2 g / cm 3 The content of zinc alloy powder in the negative electrode was 60 mass %. An alkaline dry battery was produced under the same conditions and by the same method as in Experimental Example 1, except that the produced negative electrode was used.
[0082] As shown in Table 2, the gelling agent used was cross-linked polyacrylic acid and / or partial sodium salt of cross-linked polyacrylic acid. The cross-linked polyacrylic acid used was "CARBOPOL 690" manufactured by Lubrizol Corporation. The cross-linked polyacrylic acid partial sodium salt used was "DK-500B" manufactured by Sanyo Chemical Industries, Ltd.
[0083] 10,000 batteries of each of the three types were fabricated. The initial OCV of each of the fabricated batteries was measured to determine the defective rate in the same manner as in Experimental Example 1. The composition of the gelling agent and the evaluation results are shown in Table 2.
[0084] [Table 2]
[0085] As shown in Table 2, the proportion of batteries judged as defective was low for battery A1, which used only cross-linked polyacrylic acid as a gelling agent, and battery A2, which used cross-linked polyacrylic acid and partial sodium salt of cross-linked polyacrylic acid. As in Experimental Example 1, the batteries judged as defective were those that were judged as defective due to a temporary drop in OCV, and were actually good batteries.
[0086] (Experimental Example 3) In Experimental Example 3, four types of negative electrodes were prepared by changing the type of surfactant. Except for the type of surfactant, the negative electrodes were prepared under the same conditions and methods as in Experimental Example 1. In these negative electrodes, the ratio R(75) was set to 9 mass%, and the bulk density of the zinc alloy powder was set to 3.2 g / cm 3 The content of zinc alloy powder in the negative electrode was 60 mass %. An alkaline dry battery was produced under the same conditions and by the same method as in Experimental Example 1, except that the produced negative electrode was used.
[0087] The surfactant used was polyoxyethylene alkyl ether phosphate. Polyoxyethylene alkyl ether phosphate is composed of a polyoxyethylene chain, a phosphate group bonded to one end (carbon atom) of the polyoxyethylene chain, and a linear alkyl group bonded to the other end (oxygen atom) of the polyoxyethylene chain. The polyoxyethylene chain is composed of multiple ethylene oxide groups bonded in a linear fashion.
[0088] The surfactants used were those shown in Table 3. The surfactant for battery B1 was "Phosphanol RS-410" manufactured by Toho Chemical Industry Co., Ltd. The surfactant for battery B2 was "Phosphanol RL-310" manufactured by Toho Chemical Industry Co., Ltd. The surfactant for battery B3 was "Phosphanol RD-510Y" manufactured by Toho Chemical Industry Co., Ltd. The surfactant for battery B4 was "Phosphanol RS-610" manufactured by Toho Chemical Industry Co., Ltd.
[0089] 10,000 batteries of each of the four types were produced, and the initial OCV was measured in the same manner as in Experimental Example 1. The surfactant composition and the measurement results are shown in Table 3. The number of ethylene oxide groups in Table 3 represents the number of ethylene oxide groups contained in the polyoxyethylene chain. The number of carbon atoms in the alkyl group in Table 3 represents the number of carbon atoms in the alkyl group bonded to the polyoxyethylene chain.
[0090] [Table 3]
[0091] As shown in Table 3, the defective judgment rate was particularly low when the number of ethylene oxide groups was 4 and the number of carbon atoms in the alkyl group was 12. As in Experimental Example 1, the batteries judged to be defective were those that were judged to be defective due to a temporary drop in OCV, and were actually good batteries. [Industrial Applicability]
[0092] The present disclosure can be used in alkaline dry batteries. [Explanation of symbols]
[0093] 1 Battery case 2 Positive electrode 3 negative electrode 4. Separator 5 Gasket 6 Negative electrode current collector 7 Negative terminal plate 8 Exterior Label 9. Sealing unit 10 Alkaline batteries 11 Electrolyte
Claims
1. An alkaline dry battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode comprises a zinc alloy powder, a gelling agent, a surfactant, and an electrolyte; The ratio of zinc alloy particles passing through a mesh having an opening of 75 μm in the zinc alloy powder is in the range of 9 to 28 mass %; The bulk density of the zinc alloy powder is 2.7 to 3.2 g / cm 3 is in the range of The content of the zinc alloy powder in the negative electrode is in the range of 60 to 64 mass %.
2. 2. The alkaline dry battery according to claim 1, wherein the gelling agent comprises only cross-linked polyacrylic acid, or comprises cross-linked polyacrylic acid and a partial sodium salt of cross-linked polyacrylic acid.
3. 3. The alkaline dry battery according to claim 1, wherein the surfactant comprises an anionic surfactant containing an ethylene oxide group.
Citation Information
Patent Citations
Manufacture of silver oxide battery
JP1985182657A
Production of ethanol
JP1988035531A
Manufacture of zinc-alkali battery
JP1992026067A
Alkaline battery
JP2014007002A
Zinc alloy powder for alkaline battery and alkaline battery using the same
JP2014170652A